Platelet-rich plasma in Achilles tendon healing 2 (PATH-2) trial: statistical analysis plan for a multicentre, double-blinded, parallel-group, placebo-controlled randomised clinical trial - Schlüssel, M; Keene, D; Wagland, S; Alsousou, J; Lamb, S; Willett, K; Dutton, S (BioMed Central, 2018)
Background There has been a recent steep growth in platelet-rich plasma (PRP) use for musculoskeletal conditions, but findings from high quality clinical trial data are lacking in the literature. Here, we describe the statistical analysis plan (SAP) for the Platelet-rich plasma in Achilles Tendon Healing 2 (PATH-2) trial. Methods PATH-2 is a pragmatic, parallel-group, multi-centre, double-blinded, randomised, placebo-controlled, superiority trial. The study aims to evaluate the clinical efficacy of PRP in acute Achilles tendon rupture in terms of muscle-tendon function. Patients are identified in the orthopaedic/trauma outpatient clinic. The primary outcome is muscle-tendon work capacity from the Heel Rise Endurance Test result, expressed as the Limb Symmetry Index (work, in joules), at 24 weeks post randomisation. Multivariate linear regression adjusting for the stratification factors (centre and age) and additional prognostic factors will be used to investigate the adjusted effect of the intervention. The analysis will be by modified intention-to-treat. Sensitivity analysis will assess the internal validity of the trial results by performing a per-protocol analysis. Safety will be summarised by treatment arm for all patients who started treatment. Secondary patient-reported outcome measures will be analysed using linear mixed effects models to allow all data collected at all follow-up points to be considered. Missing data will be summarised and reported by treatment arm. Missing data imputation will be performed, if appropriate. Discussion The PATH-2 trial will be reported in accordance with the CONSORT statement. This SAP publication will avoid bias arising from prior knowledge of the study results. Any changes or deviations from the current SAP will be described and justified in the final report. Trial registration ISRCTN registry: ISRCTN54992179, assigned 12 January 2015. ClinicalTrials.gov: NCT02302664, received 18 November 2014. UK Clinical Research Network Study Portfolio Database: ID 17850.